Investigating Academic Excellence in Part 1 Architectural Education through Comparison of Public Research Universities’ Program Learning Outcomes - Bahar, Bashira Mohd; Ahamad, Nurul Alia; Roslan, Siti Balkish (MAJ - Malaysia Architectural Journal, 2023)
This paper aims to evaluate the existing curriculum model in Malaysia’s architectural education system. The authors investigated the academic excellence of selected public universities by comparing their Program Learning Outcomes (PLOs), whilst considering the limitations of the research. The importance of this study is to create fruitful discussion among different architectural faculties to ensure future studies can offer a credible framework for achieving academic excellence within the Part 1 Program of the Malaysian Architectural Programs. The paper considered two mappings of PLOs against two accountable guidelines: the Manual of Accreditation for Architecture Programme (MAAP) 2013 and the Malaysian Qualification Framework (MQF) 2nd Edition 2017. The outcome of this research revealed three indispensable issues related to the PLO mappings, which are the lack of description the need to redefine the scope of certain mastery skills, and to reformulate certain PLOs to be in sync with the overall aim of the institution’s program.